Sistem Pakar Mendeteksi Kerusakan Rambut Menggunakan Basis Aturan (Rule Base Reasoning) dengan Metode Forward Chaining - Al Amin, Imam Husni; Suhartono, Suhartono (JSINBIS (Jurnal Sistem Informasi Bisnis), 2012)
One part of the human body that has a psychological role, especially in terms of self-confidence is hair. Application of expert system is designed as a tool for diagnosing hair damage. Base rules compiled into a database in such a way so as to facilitate the performance of the system. The method used in the forward chaining inference expert system to detect damage to the hair so that the user can know what kind of hair damage, solutions and how to treat them. Conformity or similarity between the results of expert diagnosis and testing of the system shows that this expert system design can be used easily, quickly and accurately. Â  Keywords : forward chaining, hair damage, the rule base reasoning, expert systems.